Optimization re-digging waste dump on exploitation Air Laya coal mine in South Sumatera, Indonesia - Pebrianto, Rosihan; Setiawan, Budhi; Ibrahim, Eddy; Sutriyono, Edy (Journal of Degraded and Mining Lands Management, 2025)
In doing slope design, paying attention to slope geometry and soil shear strength is necessary. Determination of slope geometry design also considers the balance between height and slope and production benefits. Research was conducted to analyze slope stability by testing physical and mechanical properties, limit equilibrium, and probabilistic Monte Carlo methods. The surface area of the Overburden stripping area in the 2024 RKP design amounted to 8,172.79 ????2. The production target is 2,000,000 tons of coal with a volume of overburdened material that must be stripped of 29.00, and a Stripping Ratio was obtained with a value of 14.5. The results of the overall slope evaluation of the Old Dump material with an overall slope height of 66.582 m, a slope width of 447.69 m, an overall slope of 8.32? and a bench width of 25 m, a bench height of 6 m with a ratio of 1:3 and a single slope angle of 18.43?. Then, the redesign was carried out and obtained recommendation results of 64.799 m overall slope height, 303.33 m slope width, 1,3.02? overall slope, and 25 m bench width, bench height at elevation 131-110 of 8 m with a comparison ratio of 1:2, single slope 26.57? and at elevation 110-50 of 8 m with a comparison ratio of 1:1.5, single slope 33.69.